2017
DOI: 10.1158/1078-0432.ccr-17-0618
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Gene Fusions Predicts Novel MHC Class I–Restricted T-Cell Epitopes and Immune Signatures in a Subset of Prostate Cancer

Abstract: Purpose Gene fusions are frequently found in prostate cancer and may result in the formation of unique chimeric amino acid sequences (CASQs) that span the breakpoint of two fused gene products. This study evaluated the potential for fusion-derived CASQs to be a source of tumor neoepitopes, and determined their relationship to patterns of immune signatures in prostate cancer patients. Experimental Design A computational strategy was used to identify CASQs and their corresponding predicted MHC class I epitopes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…4 At fusion level, it has been postulated that TMPRSS2:ERG fusions generate chimeric amino acid sequences that are targetable by T cells. 10 Prediction algorithms have been used to identify potentially antigenic epitopes from TMPRSS2:ERG fusions. 11 Herein, we studied the relationship between immune cell infiltration and mutations in prostate cancer by using an integrative approach combining image analysis and DNA and RNA sequencing.…”
mentioning
confidence: 99%
“…4 At fusion level, it has been postulated that TMPRSS2:ERG fusions generate chimeric amino acid sequences that are targetable by T cells. 10 Prediction algorithms have been used to identify potentially antigenic epitopes from TMPRSS2:ERG fusions. 11 Herein, we studied the relationship between immune cell infiltration and mutations in prostate cancer by using an integrative approach combining image analysis and DNA and RNA sequencing.…”
mentioning
confidence: 99%
“…Finally, gene fusions in prostate cancer can result in the formation of unique chimeric amino acid sequences that span the breakpoint of the two fused gene products and potentially generating fusion proteins with neoepitopes. In a recent computational study, type VI TMPRSS2-ERG gene fusions contained high-affinity HLA-restricted epitopes and were recognized by CD8+ T-cells in vitro ( 54 ). Though these mechanistic possibilities are intriguing, it is also possible that the association of higher lymphocyte densities with ERG rearrangement is due to a confounding additional molecular alteration, which is itself associated with ERG fusion.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the Tmprss2-Erg fusion promotes recruitment of regulatory T cells to the tumor site [50]. Recent studies have shown an association between low levels of TILs comparing TMPRSS2-ERG fusions producing chimeric transcripts in the coding in the fusion-positive cases results in suppression of immune response by alteration of cytokine production [51,52].…”
Section: Phosphatase and Tensin Homologue (Pten)mentioning
confidence: 94%